Contrastive Analysis of Verb Suffix Formation in Indonesian And German Language - Hasmawati, Hasmawati; Rijal, Syamsu; Angreany, Femmy (Phonologie : Journal of Language and Literature, 2024)
Abstract. The main concern of the study is the verb construction process through suffixes in Indonesian and German by using contrastive analysis. The primary purpose of this study is to find the types of suffixes that can be used to build the verb in both languages, namely the Indonesian and German. By using a literature review and contrastive analysis approach, the similarities and the distinction between the two languages can be shown, so as to facilitate typical Indonesian students to learn the German language or vice versa. The results of the study showed that verb suffix construction in Indonesian consists of suffix i- and suffix –kan, both of which foster the imperative verbs (commands). Meanwhile, the verb suffix formation in German consists of suffix -el,-er, and-ig. The three suffixes can form the verb if they are attached to verbs, nouns and adjectives. In addition to all three suffixes, there are also other suffixes that often attach to verbs when conjugated, such as, the suffix –e, -st (-est),-t (-et), and -en for the present tense (Prӓsen) and the suffix –te, -test (-etest), -tet (-etet), -ten (-eten) for past tense (Prӓteritum) in regular verbs.Keyword: verb, suffixes, Indonesian, German, contrastive analysis